The British and Irish Ruling Class 1660-1945 Vol. 2 - Wasson, Ellis A. (De Gruyter, 2021)
The book provides a comprehensive reference source for the governing class of Great Britain and Ireland from Oliver Cromwell to Winston Churchill, and offers a deep pool of data to support analysis of social, political, economic, and cultural history in the British Isles over the course of more than four centuries.